Identifying a Comprehensive ceRNA Network to Reveal Novel Targets for the Pathogenesis of Parkinson's Disease - Zhang, Xi; Feng, Shengyu; Fan, Yu; Luo, Yuping; Jin, Lingjing; Li, Siguang (Frontiers in Neurology, 2020)
Parkinson’s disease (PD) is the second commonest progressive neurodegenerative disease worldwide. Increasing evidence reveals that noncoding RNAs play roles in the pathophysiological process of PD. This study aim is to construct lncRNA-associated ceRNA networks in PD, which might have the potential to clarify the pathogenesis. We investigated differental expression genes (DEGs) in substantia nigra array data between PD patients and healthy controls (HCs) from the Gene Expression Omnibus (GEO) database. Based on DEGs and predicted miRNAs, we constructed the ceRNA network and performed functional annotations of mRNAs in the network. Hub genes were identified through protein‐protein interaction (PPI) network and clustering analysis called MCODE. Then the key ceRNA subnetwork was constructed based on these genes and their positively correlated lncRNAs and verified in independent GEO datasets and literatures. As a result, we identified 31 differentially expressed (DE) lncRNAs and 1828 DEmRNAs and finally constructed the ceRNA network associated with PD, including 9 lncRNAs,18 miRNAs and 185 mRNAs. mRNAs in the ceRNA network focused on autophagy, DNA repair and vesicle transport, which were critical pathological processes in PD. To clarify the core part in the ceRNA network, 19 hub genes that play key roles in autophagy, DNA repair and vesicle transport were gained through PPI and MCODE analyses. Then lncRNA-mRNA pairs with significantly positive correlation were used to build the core ceRNA subnetwork which was verified in published literatures and other PD datasets. In conclusion, the substantia nigra lncRNA-associated ceRNA network of PD was constructed, and the core ceRNA subnetwork was also identified. These ceRNA networks regulate autophagy, DNA repair and vesicle transport in PD. Our findings improve the current understanding of ceRNA biological behaviors and the regulatory roles in the pathogenesis of PD and provide promising diagnostic biomarkers.